Pengaruh Lokasi, Biaya Dan Fasilitas Sekolah Terhadap Keputusan Orang Tua Memilih SD Swasta Talitakum - Feberiyus Waruwu; Dedy Lazuardi; Dian Setyorini (Jurnal Minfo Polgan, 2026)
This study examines the factors influencing parents’ decisions in selecting private elementary schools, particularly at SD Swasta Talitakum, which has experienced a decline in student enrollment in recent years. This condition reflects a shift in parents’ preferences in choosing schools for their children amid increasing competition among educational institutions. The objective of this study is to analyze the effect of location, education costs, and school facilities on parents’ decisions. This research employs a quantitative approach using a survey method. The population consists of all parents of students at SD Swasta Talitakum, totaling 111 respondents, using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS, along with validity, reliability, and classical assumption tests. The results indicate that partially, location and school facilities have a positive and significant effect on parents’ decisions, while education costs have no significant effect. Simultaneously, all variables significantly influence parents’ decisions. The Adjusted R Square value of 0.215 indicates that the model explains 21.5% of the variation in parents’ decisions, while the remaining is influenced by other variables outside the model. This study contributes empirically to the field of educational management and provides practical insights for schools to improve competitiveness through enhancing facilities and accessibility.